Menilai Dampak Evaluasi Produk Konsumen dan Kepercayaan Pada Niat Pembelian Kembali Pada Lingkungan E-Commerce - Pratiwi, Dwi Indah (E-Jurnal Akuntansi, 2019)
This study aims to analyze the factors that influence repurchase intentions in e-commerce. This research method uses quantitative descriptive method by distributing questionnaires as a method of data acquisition. T he data analysis t echnique uses multiple linear regression. Data were obtained by 96 respondents from various Indonesian respondents through a web-based questionnaire. The results showed that the p erceived trust, p erceived usefulness, p erceived competitive prices, had a significant and positive relationship with the intention to buy back in e-commerce.While p erceived risk does not have a significant relationship with repurchase intention. Keywords : E-commerce; Repurchase Intention; Perceived Consumer.